2016
DOI: 10.1007/jhep07(2016)078
|View full text |Cite
|
Sign up to set email alerts
|

Lepton Flavor Violation in the singlet-triplet scotogenic model

Abstract: We investigate lepton flavor violation (LFV) in the the singlet-triplet scotogenic model in which neutrinos acquire non-zero masses at the 1-loop level. In contrast to the most popular variant of this setup, the singlet scotogenic model, this version includes a triplet fermion as well as a triplet scalar, leading to a scenario with a richer dark matter phenomenology. Taking into account results from neutrino oscillation experiments, we explore some aspects of the LFV phenomenology of the model. In particular, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 77 publications
(110 reference statements)
1
23
0
Order By: Relevance
“…For instance, scenarios with light scotogenic states and sizable Yukawa couplings lead to observable lepton flavor violating (LFV) processes in the next round of experiments [40]. In this case, bounds from LFV searches set strong constraints, to be added to those discussed in this paper.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For instance, scenarios with light scotogenic states and sizable Yukawa couplings lead to observable lepton flavor violating (LFV) processes in the next round of experiments [40]. In this case, bounds from LFV searches set strong constraints, to be added to those discussed in this paper.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…ii) Regarding fermion DM, the lightest eigenvalue χ 0 1 that comes from the mixing between the triplet component Σ 0 and the fermion singlet N is the DM candidate. In this case, we have a interesting phenomenology that comes from the mixing between the singlet and the triplet fermion [9,15,16]. Even more, some important features of this DM candidate are based on its nature itself.…”
Section: Dark Matter Candidatesmentioning
confidence: 99%
“…(LFV) processes, such as l α → l β γ, 3-body decays as µ → 3e, and µ − e conversion in nuclei that imply strong constraints on the parameter space [15]. Also, it was shown that the STFDM model is consistent to high energies.…”
Section: Scalars Fermions Particlementioning
confidence: 99%
See 2 more Smart Citations